Condutividade elétrica de sementes de camomila em resposta ao tempo de embebição e tamanho da amostra - Galvani, Raquel [UNESP]; Almeida, Tatiana Rezende Pires de [UNESP]; Toledo, Mariana Zampar; Ming, Lin Chau [UNESP] (My University, 2012)
Electrical conductivity has been proposed as a rapid test to evaluate seed vigor; however, few researches have emphasized methodologies to its use in seeds of medicinal plants, such as chamomile. The objective of the research was to evaluate the electrical conductivity of chamomile seeds affected by different imbibition times and sample size. The evaluations consisted of moisture content, germination and vigor (first count of germination) to seed initial characterization. Then, it was evaluated the electrical conductivity, affected by imbibition time (6, 12, 24 e 48 hours) and seed amount per sample (25, 50, 75, 100). The completely randomized design was used with four replications, arranged as a 4 x 4 factorial. Means were compared by the Tukey test at 5% of probability. It was concluded that the electrical conductivity of chamomile seeds is affected by the number of seeds per sample and imbibition time isolately.

A condutividade elétrica tem sido proposta como um teste rápido para avaliar o vigor das sementes; entretanto, poucos estudos têm enfatizado metodologias para sua utilização em sementes de plantas medicinais, como a camomila. O trabalho objetivou avaliar a condutividade elétrica de sementes de camomila em resposta à diferentes tempos de embebição e tamanho da amostra. As avaliações constaram do teor de água, germinação e vigor (primeira contagem da germinação) para caracterização inicial das sementes. Posteriormente foi avaliada a condutividade elétrica, em função do tempo de embebição (6, 12, 24 e 48 horas) e quantidade de sementes por amostra (25, 50, 75, 100). O delineamento foi inteiramente casualizado com quatro repetições, em esquema fatorial 4 x 4. As médias foram comparadas através do teste de Tukey a 5% de probabilidade. Concluiu-se que os resultados do teste de condutividade elétrica variam em função do número de sementes por amostra e tempo de embebição isoladamente.
Electrical conductivity of chamomile seeds as affected by imbibition time and sample size
Keywords: Chamomilla recutita; Medicinal plants; Vigor; Chamomilla recutita; Plantas medicinais; Vigor